ANALYSIS OF SERVICE QUALITY AND PRICE PERCEPTION ON CUSTOMER LOYALTY WITH PERCEIVED VALUE AS A MEDIATING VARIABLE AMONG VISITORS OF VILLA STAR HOMESTAY TAKENGON - Yulia; Erwansyah Erwansyah; Muhammad Dharma Tua Putra Nasution (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study examines the effects of service quality and price perception on customer loyalty, with perceived value serving as a mediating variable among visitors to Villa Star Homestay Takengon. The research is motivated by the growing importance of understanding the determinants of customer loyalty in the hospitality sector amid intensifying competition and rising expectations for service excellence and price fairness. Employing a quantitative approach, data were collected from 155 guests and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicate that service quality does not directly influence customer loyalty but significantly affects perceived value. In contrast, price perception has a positive and significant impact on both perceived value and customer loyalty. Furthermore, perceived value significantly mediates the relationships between service quality, price perception, and customer loyalty. These results highlight perceived value as a key mechanism linking service and pricing factors to loyalty formation. Theoretically, this study reinforces Value-Based Marketing and Price Fairness Theory by emphasizing the strategic importance of perceived value. Practically, it offers managerial implications for hospitality businesses, suggesting that enhancing perceived value through superior service and fair pricing can effectively strengthen long-term customer loyalty.